2021
DOI: 10.3390/metabo11010049
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylornithine Membrane Lipids: Discovered in Planctomycetes and Identified in Diverse Environments

Abstract: Intact polar membrane lipids (IPLs) are the building blocks of all cell membranes. There is a wide range of phosphorus-free IPL structures, including amino acid containing IPLs, that can be taxonomically specific. Trimethylornithine membrane lipids (TMOs) were discovered in northern wetland Planctomycete species that were isolated and described in the last decade. The trimethylated terminal nitrogen moiety of the ornithine amino acid in the TMO structure gives the lipid a charged polar head group, similar to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Structurally ( Fig. 9 ), they are composed of a 3-FAHFA bound to the amine group of an amino acid(lysine [ 286 ], glycine [ 287 ], ornithine [ 288 , 289 ], di- and tri-methylated ornithine [ 290 ]) or dipeptide such as in flavolipin (a serine-glycine polar head and a omega-1 methyl group on both fatty chains)[ 267 ] or cerilipin [ 286 , 291 ].…”
Section: Fatty Acid Esters Of Hydroxy Fatty Acidsmentioning
confidence: 99%
“…Structurally ( Fig. 9 ), they are composed of a 3-FAHFA bound to the amine group of an amino acid(lysine [ 286 ], glycine [ 287 ], ornithine [ 288 , 289 ], di- and tri-methylated ornithine [ 290 ]) or dipeptide such as in flavolipin (a serine-glycine polar head and a omega-1 methyl group on both fatty chains)[ 267 ] or cerilipin [ 286 , 291 ].…”
Section: Fatty Acid Esters Of Hydroxy Fatty Acidsmentioning
confidence: 99%
“…Betaine lipids, typical of lower plants and of some cyanobacteria (Klug & Benning, 2001 ; Řezanka et al, 2004 ), were abundant at all sites, representing up to 30% of total IPLs (Figure 2C ). High relative levels of ornithine lipids, particularly trimethyl ornithine lipids that are exclusive bacterial markers (López‐Lara & Geiger, 2017 ; Moore, 2021 ), were observed in BSCs of sites 2, 3 and 6 (relative abundance range, 2%–3.8%). Even though eukaryotic biomass (e.g., mosses, lichens and bryophytes) was not visible in BSCs, the detection of sterols revealed its presence.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, DLs were enriched in Actinobacteria, Proteobacteria and Acidobacteria phyla which are among the most abundant taxa inhabiting bare soils of cold deserts worldwide (Bourquin et al, 2022;Leung et al, 2020) and were found in other Himalayan forefields (Srinivas et al, 2011). The limited dispersion and homogenous selection resulted in being the main ecological processes in the assembly of microbial communities in BSC and DL, suggesting that bacteria had a life-death dynamics that allowed community composition to drift apart due to spatial isolation between sites (Fodelianakis et al, 2020;2021), as it was also observed in permafrost-associated microbiomes in Alaskan forests (Bottos et al, 2018). The rejection of the neutral community model for both BSC and DL and of the source-sink hypotheses support that bacterial community assembly is mainly deterministic rather than stochastic and it is driven by environmental factors and microbial species interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleoside and Nucleotide biosynthesis, cofactor, carrier and vitamin biosynthesis, Amino acid biosynthesis, and Fatty acid and lipid biosynthesis were shown as critical pathways responsible for microbial proliferation and buildup in compost. The Nucleosides and Nucleotides are required for cell growth and replication pathways, while amino acids, fatty acids, and lipids are building blocks for microbial cell structure [ 60 – 62 ]. Cofactors, carriers, and vitamins play a critical role in microbial enzymatic functions, ultimately directly influencing nutrient cycling through catabolic and anabolic processes within the available pool of nutrients in the compost environment [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%